O ensino de história local nos anos iniciais do ensino fundamental na proposta curricular do município de Cascavel (2008 - 2021) - Silva, Clenilza Lemos da (2022)
This dissertation discusses Local History in the Early Years of Primary Education in the Municipal Public Teaching Network of Cascavel - PR, from the introduction of the Curriculum (2008), which content was intended for the students of the 4th Year. With the approval of the National Common Curricular Base and the readjustment of the Curriculum for the Municipal Public Teaching Network of Cascavel (2020), the content about Local History was anticipated to the 3rd Year of Elementary School - Early Years. The objective of this work is to contribute to the teaching and learning processes, considering the periodization of human development in the first stage of elementary school. The methodology to accomplish what is proposed will be through a qualitative approach based on bibliographic and documental sources. The silencing about certain local events, the systematic devaluation of History teaching, and the generalizations about certain statements, produced by the traditional historiography, positivist-based, were responsible for a narrative in the form of History writing based on the great deeds of the dominant class and its representatives. The teaching of Local History presents itself as a starting point of great relevance, by working with the nearby reality, giving voice to those who were marginalized by the "Official History". It is considered that, when it comes to the teaching of Local History, there is a certain challenge between what is proposed in the curriculum of the city of Cascavel and what is developed in schools. In this regard, it is worth highlighting some points: 1. the absence of a systematized approach about Local History and its importance in the formation of the student; 2. increase investments in teacher training and pedagogical resources; 3. deepen the studies about the theoretical and methodological conception of the curriculum proposal of the Municipality. Finally, we identify the need to guarantee to the student the understanding of the processes of transformation and permanence throughout time in the construction of historical knowledge, as well as with respect to the theoretical-methodological guidelines proposed in the document. It is considered, therefore, that the teaching of Local History presents weaknesses in the scope of school work, as proposed in the curriculum of the Municipality.